PSYKOTERAPEUTERS VANSKELIGHEDER OG SUPERVISORERS KOMPETENCE - Friis Jørgensen, Eric; Elsass, Peter (Psyke & Logos, 2022)
Based on a questionnaire concerning 157 Danish psychotherapists' career development, this article discusses supervisors' competence to alleviate therapists' difficulties. The Danish study is carried out within the framework of a cooperating internatinal research network (Collaborative Research Network, in itself a part of Society for Psychotherapy Research). At present the questionnaire includes about four thousand respondents worldwide. Processes in the therapeutic triad (client, supervisee, supervisor) are discussed in the article focusing on working alliances between supervisee and supervisor. Resistance, tranference and counter transference are considered in relation to supervisee and supervisor. Supervision and supervisor instruction are looked at in the context of ensuring quality, which is why an evaluation of supervisees' and supervisors' competence is included. Importance is attached to using empirically based knowledge where possible, founded on both national and international material.